Nanomaterial in Food Packaging: A Comprehensive Review. (24th August 2022) - Barage, Sagar; Lakkakula, Jaya; Sharma, Arushi; Roy, Arpita; Alghamdi, Saad; Almehmadi, Mazen; Hossain, Md. Jamal; Allahyani, Mamdouh; Abdulaziz, Osama
Abstract : Food packaging industry is going through various scientific evolutions as per the preferences of the consumers along with the consumer trends. Current trends focus on not only protecting the food intelligently but also making it visually appealing to the consumer. In recent years, considerable attention is been given to replace nonbiodegradable materials with ecofriendly biodegradable composite material. Nanotechnology is flourishing and has proven to be a great incorporation to the packaging industry, as it can also overcome the drawbacks of the existing methods. Various nanomaterials have been explored and tested for manufacturing of packaging materials. In the present review, we discussed on current trends in food packaging and their drawbacks with respect to over consumption of plastic and how sustainable packaging is being implemented. Furthermore, nanotechnology is becoming a promising and widely used potential in food packaging industry along with nanomaterials currently being used such as zinc nanoparticles, polymer clay nanoparticles, and silver nanoparticles in food packaging. This information will broaden our current understanding on potential and problems associated with nanotechnology in food packaging.